Benchmarking visit by the Faculty of Medicine Universitas Islam Sultan Agung Semarang to the Faculty of Medicine and Hospital Al-Sultan Abdullah, Universiti Teknologi MARA - Ab Wahab, Sabrina; Abd Ghafar, Mohd Zaquan Arif; Abdul Rani, Rafiz (Faculty of Medicine, 2024)
On a Wednesday morning, 21stFebruary 2024, the Faculty of Medicine Universitas Islam Sultan Agung Semarang delegation arrived at the prestigious Hospital Al-Sultan Abdullah, Universiti Teknologi MARA (UiTM). The day commenced with the arrival of the delegation from the Faculty of Medicine, UNISSULA, followed by a warm welcoming address by Associate Professor Dr. Fazah Akhtar Hanapiah, the Dean of the Faculty of Medicine, UiTM set the tone for the day ahead. A speech from Dr. dr. H. Setyo Trisnadi S.H., Sp., Dean of the Faculty of Medicine UNISSULA, expressed his gratitude for the opportunity to visit and learn from their esteemed counterparts, emphasizing the importance of such academic exchanges in advancing medical education and research.